2018
DOI: 10.1016/j.cell.2018.01.020
|View full text |Cite|
|
Sign up to set email alerts
|

Cloning of Macaque Monkeys by Somatic Cell Nuclear Transfer

Abstract: Generation of genetically uniform non-human primates may help to establish animal models for primate biology and biomedical research. In this study, we have successfully cloned cynomolgus monkeys (Macaca fascicularis) by somatic cell nuclear transfer (SCNT). We found that injection of H3K9me3 demethylase Kdm4d mRNA and treatment with histone deacetylase inhibitor trichostatin A at one-cell stage following SCNT greatly improved blastocyst development and pregnancy rate of transplanted SCNT embryos in surrogate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(177 citation statements)
references
References 42 publications
(44 reference statements)
3
159
0
4
Order By: Relevance
“…Recently, the importance of epigenetic modification in regulating somatic cell reprogramming as well as early embryo development has been widely reported (Liu et al, 2018;Matoba & Zhang, 2018;Yu et al, 2017). However, only a handful of studies have indicated that epigenetic modification plays an important role in controlling oocyte PCD during PF pool establishment (Sun et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the importance of epigenetic modification in regulating somatic cell reprogramming as well as early embryo development has been widely reported (Liu et al, 2018;Matoba & Zhang, 2018;Yu et al, 2017). However, only a handful of studies have indicated that epigenetic modification plays an important role in controlling oocyte PCD during PF pool establishment (Sun et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The preimplantation embryo is therefore a valuable research model for epigenetic scientists to dissect physiologic relevance of epigenetic modifications. Increasing evidence has demonstrated that incomplete epigenetic reprogramming is a major contributing factor to developmental failure or poor developmental outcome associated with the use of assisted reproductive technologies (12)(13)(14). Indeed, reproductive cloning of macaque monkeys via somatic-cell nuclear transfer is feasible when H3K9me3 demethylase [lysine demethylase 4D (KDM4D)] is employed to correct H3K9me3 level (12).…”
mentioning
confidence: 99%
“…This is as important a factor as the continued development of efficient genetic tools adapted to NHP. Another factor of major importance in the continued development of genetically modified NHP models of neurological and neuropsychiatric disorders is the support of the general public and of funding agencies, such as the U.S. National Institutes of Health and its Primate Research Centers, the Japanese Consortium BRAIN/Minds – which uses the marmoset as the main animal model for neuroscience research (Okano et al, 2015; Okano et al, 2016), and the recent but very accelerated development of NHP research in China (Liu et al, 2018). While much of the applications of genetically engineered NHP to biomedical research are only now emerging, the relatively few reports to date show that this effort has a tremendous potential to impact our understanding of human disease and to advance the development of effective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The successful generation of cloned cynomolgus macaques by somatic cell nuclear transfer (SCNT) using both fetal fibroblasts and adult cumulus cells has just been reported (Liu et al, 2018). This follows many years of pioneering efforts, including production of rhesus macaques from blastomere transferred embryos (Meng, Ely, Stouffer, & Wolf, 1997), establishment of rhesus ESC derived from SCNT embryos (Byrne et al, 2007), and modification of the SCNT approach for improved nuclear remodeling (Mitalipov et al, 2007; Sparman, Tachibana, & Mitalipov, 2010).…”
Section: Introductionmentioning
confidence: 99%